Effect of oxygen stoichiometry on the threshold switching of RF-sputtered NbOx (x = 2.0–2.5) films. (December 2021) - Aziz, Jamal; Kim, Honggyun; Rehman, Shania; Hur, Ji-Hyun; Song, Yun-Heub; Khan, Muhammad Farooq; Kim, Deok-kee
Highlights: The Poole-Frenkel induced threshold switching of the NbOx films is controlled by changing the oxygen content (x = 2.0 ∼ 2.5). The synthesis method is simple and low-cost. The films exhibit excellent uniformity. The films exhibit thermal stability upto 160°C. Abstract: In this study, we report the Poole-Frenkel induced threshold switching characteristics of niobium dioxide (NbO2 ) films by tuning oxygen stoichiometry. Similar to correlated oxides, NbO2 is also found sensitive to oxygen related defects. The oxygen stoichiometry of NbO2 films was varied by changing the oxygen flux during its synthesis in reactive RF-sputter. Nb2 O5 dominant phase of as-grown films was detected during Raman spectroscopy. For the reduction of Nb2 O5 films, we chose tungsten as a top electrode due to its considerable oxygen affinity. After the required forming process, stable threshold switching was observed which is attributed to the reduction of Nb2 O5 phase to NbO2 due to interfacial WOx layer formation between top electrode and Nb2 O5 . Increase of O2 flux during deposition leads to an increase in the selectivity, threshold voltage and off-state resistance. These devices showed good thermal stability up to 160 °C making them useful for RRAM and neuromorphic computing applications. Graphical abstract: Image, graphical abstract